2019
DOI: 10.1097/ajp.0000000000000783
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Moderating the Relationship Between Pain and Health Care Use in Youth With Sickle Cell Disease

Abstract: Objective:The purpose of the current study was to investigate the influence of sleep on the relationship between pain and health care use (HCU) in youth with sickle cell disease (SCD). It was hypothesized that poor sleep would be related to higher HCU and would strengthen the relationship between high pain frequency and more HCU among youth with SCD.Methods: Ninety-six youth with SCD (aged 8-17 years), and their guardians, were recruited from three regional pediatric SCD clinics. Guardians reported on the yout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
3
4
0
Order By: Relevance
“…This suggests that patients with a history of frequent acute pain events may benefit from a formal assessment of sleep. These data are in contrast to one prior study that reported that poor sleep quality did not strengthen the relationship between high pain frequency and more healthcare utilization in youth with SCD 21 . Additionally, females demonstrated significantly higher sleep‐related impairment PROMIS scores than males, which is consistent with prior literature in healthy patients 33 …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This suggests that patients with a history of frequent acute pain events may benefit from a formal assessment of sleep. These data are in contrast to one prior study that reported that poor sleep quality did not strengthen the relationship between high pain frequency and more healthcare utilization in youth with SCD 21 . Additionally, females demonstrated significantly higher sleep‐related impairment PROMIS scores than males, which is consistent with prior literature in healthy patients 33 …”
Section: Discussionsupporting
confidence: 84%
“…20 While prior studies have examined the association between sleep and pain in children with SCD, these studies have produced mixed results and typically focused on sleep apnea, duration, and efficiency. [21][22][23] We have observed late mid-sleep times and substantial social jetlag among adolescents and young adults with SCD. 24 Yet, few studies have examined these circadian factors and their potential impact on pain in the context of SCD.…”
Section: Introductionmentioning
confidence: 91%
“…Our data revealed the strong relationship between sleepiness and HRQOL and suggest incorporating measures to explore coping in relation to sleep difficulties (e.g., sleep-disordered breathing) and sleep hygiene behaviours (e.g., bedtime routine) may be a valuable addition to coping interventions for children with SCD. Our findings add to a growing body of literature that has demonstrated that more sleep disturbances (i.e., parasomnias and movement at night) were related to greater daytime sleepiness (Kölbel et al, 2020 ) and that there is a bi-directional relationship between poor night-time sleep quality and higher daytime pain in youth with SCD (Valrie et al, 2020 ). Expanding upon the influence of sleep, fatigue (a feeling of tiredness or exhaustion) has also been shown to be more strongly related to cognitive deficits in children with SCD (Rogers et al, 2017 ).…”
Section: Discussionsupporting
confidence: 70%
“…Guardians reported healthcare utilization during the Structured Pain Interview for Parents (SPI‐P). To assess healthcare utilization due to pain within the past year, three items were used: (a) “How many times have your child gone to see a doctor?” (b) “Number of times your child has been hospitalized,” and (c) “Number of emergency room visits.” The SPI‐P measure has been used extensively for assessing healthcare use in youth with SCD and has acceptable interrater and test–retest reliability over a 9–12‐month period 30,37,38 …”
Section: Methodsmentioning
confidence: 99%
“…The SPI-P measure has been used extensively for assessing healthcare use in youth with SCD and has acceptable interrater and test-retest reliability over a 9-12-month period. 30,37,38…”
Section: Intrapersonal Factorsmentioning
confidence: 99%